Ineffectiveness of Price Sensitivity and Competitive Landscape in Luxury Goods Impulse Buying - Hopuntius, Virgin Fermalia Fiondi (BIMA Journal (Business, Management, & Accounting Journal), 2024)
Purpose: This study examines the moderating role of price sensitivity and competitive landscape on the relationship between price discount, limited-quantity scarcity, and limited-time scarcity with impulse buying in the context of luxury goods. Methodology: This research applied a quantitative approach. A purposive sampling technique was used to collect the sample, resulting in 210 Indonesian respondents being selected. A questionnaire with a seven-point Likert scale was used to collect data. Structural Equation Modeling (SEM) with AMOS 26 was used to process the data. Results: The results reveal that price discount, limited-quantity scarcity, and limited-time scarcity do not significantly influence impulse buying of luxury goods. Additionally, price sensitivity and competitive landscape do not moderate these relationships, indicating that the psychological drivers of impulsive purchasing for luxury products differ from those of mainstream goods. Findings: The absence of moderation by price sensitivity and competitive landscape suggests that luxury consumers prioritize brand value, exclusivity, and quality over promotion strategies. Novelty: The study contributes to a nuanced understanding of consumer behavior in the luxury market by demonstrating that price sensitivity and competitive landscape do not function as a key driver of impulse buying in this segment. Originality: This research explores the interaction between price sensitivity and scarcity tactics in the luxury goods sector, offering a new perspective on marketing strategies for high-end brands. Conclusion: Marketers of luxury goods should focus less on promotion tactics and more on emphasizing exclusivity and quality to drive consumer engagement. Type of Paper: Empirical Research Article.